Prognostic role of neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and systemic immune inflammation index in acute ischemic stroke: A STROBE-compliant retrospective study. Issue 25 (25th June 2021) - Li, Li-Hua; Chen, Chung-Ting; Chang, Yun-Chin; Chen, Ying-Ju; Lee, I-Hui; How, Chorng-Kuang
Abstract : Abstract: The acute ischemic stroke (AIS) is a devastating disease and remains the leading cause of death and disability. This study aims to evaluate the role of hematological inflammatory markers (neutrophil-to-lymphocyte ratio [NLR], platelet-to-lymphocyte ratio [PLR], and systemic immune inflammation index [SII]) in predicting the neurological recovery in acute cerebrovascular events over 1-year follow-up. Adult patients diagnosed with AIS within 3 hours from January 2016 to December 2018 were recruited retrospectively. The modified Rankin Scale (mRS) was recorded upon admission to the emergency department (ED) and 1, 3, 6, and 12 months after a stroke. The primary outcome measure was the neurological recovery. The neurological recovery was defined as an improvement in mRS score ≥ 1 compared with that at the ED admission baseline. A total of 277 consecutive adult patients with AIS within 3 hours were enrolled. The initial average of the National Institute of Health Stroke Scale was 9.2 ± 7.8, and 90.3% of patients had an mRS ≥ 2 at ED admission baseline. The overall neurological recovery rates of 48.7%, 53.7%, 59.2%, and 55.9% were observed at 1, 3, 6, and 12 months follow-up, respectively. The multivariate analysis revealed that the baseline NLR value was a significant predictor of neurological recovery at 3 months after a stroke (adjusted odds ratio = 0.89, 95% confidence interval = 0.80–0.99, P  = .035). A low NLR at ED admission could be useful marker for predicting neurological recovery at 3 months after stroke.